Investigate engineering properties of modified open-graded asphalt mixtures. Issue 1 (1st January 2019) - Asmael, Noor Moutaz
Abstract: Open-Graded Friction Course mixture (OGFC) has a gap-graded aggregate that results in highly air voids. This structure provides higher permeability by allowing water to flow through it. Although these mixtures have good drainage properties, they exhibit poor strength with a short life span. Because of their poor performance, there is a lack to be used in pavement application. Attempts had made to increase mixture performance; one of these methods is by using fibers or polymers. The objective of the current study is to determine if modified OGFC mixes with different polymers and fibers have comparable performance. Polymers and fibers were used in OGFC mixes to evaluate their performance. Steel fiber, glass fibers, Polyvinyl chloride (PVC) and Phenol resin were investigated in this study. The modified mixtures were tested by indirect tensile strength, Marshall and permanent deformation tests. Results showed that fibers decrease rutting by 19% and they have more effective than polymers that decrease rutting by 7%, and glass fiber was found to be more effective with a 24% reduction in permanent deformation than other additives to enhance performance.